2013
DOI: 10.1155/2013/681891
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Effect of Ethanol Extract of Polish Propolis on Mutans Streptococci and Lactobacilli Isolated from Saliva

Abstract: Dental caries occurrence is caused by the colonization of oral microorganisms and accumulation of extracellular polysaccharides synthesized by Streptococcus mutans with the synergistic influence of Lactobacillus spp. bacteria. The aim of this study was to determine ex vivo the antibacterial properties of ethanol extract of propolis (EEP), collected in Poland, against the main cariogenic bacteria: salivary mutans streptococci and lactobacilli. The isolation of mutans streptococci group bacteria (MS) and Lactoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 46 publications
3
75
0
2
Order By: Relevance
“…Over time, it has been marketed in various forms, such as toothpastes, mouthrinses, and lozenges. Propolis extract is known to possess antimicrobial activity against Streptococcus mutans, a Gram-positive cocci, facultative anaerobic strains commonly found in the human oral cavity, and a significant contributor to plaque formation [13, 14]. Propolis has been also found beneficial in the treatment of gingivitis and oral mucosa lesions in case studies and pilot clinical studies [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Over time, it has been marketed in various forms, such as toothpastes, mouthrinses, and lozenges. Propolis extract is known to possess antimicrobial activity against Streptococcus mutans, a Gram-positive cocci, facultative anaerobic strains commonly found in the human oral cavity, and a significant contributor to plaque formation [13, 14]. Propolis has been also found beneficial in the treatment of gingivitis and oral mucosa lesions in case studies and pilot clinical studies [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of studies demonstrated that propolis reveals substantial properties, including the promotion of soft tissues healing and regeneration/reparation. Apart from its antibacterial [1][2][3][4][5][6], anti-inflammatory [7,8], antioxidant [9][10][11], immunoprotective [12], hepatoprotective activities [13,14], propolis has also anti-proliferative [15][16][17][18][19] and proapoptotic ones [20][21][22][23]. Composition of propolis is diverse and depends on both place of origin and time in which it has been collected.…”
mentioning
confidence: 99%
“…The essential oils have the ability to inhibit the plaque formation, as they demonstrate not only antimicrobial effect, provided mostly by the aromatic agents, but they also have deeper penetration in the biofilm, compared to other agents, such as stannous fluoride and triclosan [4,5,6]. There are many antimicrobial agents, most of them designed for home use, where there is no dosage control, frequency and intended use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are many antimicrobial agents, most of them designed for home use, where there is no dosage control, frequency and intended use. Quite naturally, their efficiency is subject of discussion in many scientific reports [4,5], as the general opinion is that they can be successfully used as supplementary, but not as primary agents for caries prophylactics. In relation with overcoming the microbial resistance, a number of authors comment on limitation the use of antimicrobial agents not only to high-risk patients, but also only to high-risk dentition areas [4,5].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation